A Method for Evaluation of Streetscapes: Relationship between Visual Entropy and Interesting Streetscape - Karimimoshaver, Mehrdad; Khazaei, Fereshteh (International Journal of Architectural Engineering Technology, 2023)
The present research studies the complexity of urban facades, which is related to the visual diversity and correlation of the components of urban facades. It studies how the complexity of urban facades affects their desirability amongst citizens and what their preferences are when it comes to facade complexity. In addition, it addresses the complexity of urban facades in both quantitative and qualitative forms and investigates the relationship between quantitative and qualitative data and the desirability of using the correlation analysis method in urban facades. To obtain quantitative data, a survey was conducted on Nowshahr citizens, and the data was analyzed through MATLAB software. The data obtained is the image entropy, which indicates the number of image irregularities. The results indicated that the Nowshahr citizens prefer the second complexity level, then the first complexity level, followed by the third complexity level, and finally the fourth complexity level, respectively. There is a slight correlation in the results of the quantitative-qualitative data comparison. Therefore, using entropy as a measure of complexity cannot be confirmed in this study, and further research is needed.